2016
DOI: 10.1186/s13071-016-1734-8
|View full text |Cite
|
Sign up to set email alerts
|

The importance of male body size on sperm uptake and usage, and female fecundity in Aedes aegypti and Aedes albopictus

Abstract: BackgroundAdult mosquito density is a critical factor in the transmission of arboviruses by container Aedes spp. mosquitoes. Female fecundity drives population growth, and therefore contributes to adult mosquito density. Previous studies have focused on female body size as the major determinant of fecundity, paying little attention to male condition. In this study, we examined the effects of male body size on the abundance of sperm in spermatheca, depletion of sperm over time, and female fecundity.MethodsWe ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 48 publications
2
19
2
Order By: Relevance
“…Smaller females have reduced fecundity, have been shown to require multiple blood feeds before completion of a gonotophic cycle and may be less attractive to males (34,39,53,54). Although we found no difference in overall insemination rates in relation to larval cooling, inseminated An.…”
Section: Discussioncontrasting
confidence: 59%
“…Smaller females have reduced fecundity, have been shown to require multiple blood feeds before completion of a gonotophic cycle and may be less attractive to males (34,39,53,54). Although we found no difference in overall insemination rates in relation to larval cooling, inseminated An.…”
Section: Discussioncontrasting
confidence: 59%
“…Further, nutrient availability and daily temperature regimes can vary significantly among active breeding containers distributed in the same household area (Hemme et al, 2009). Despite shared genetic ancestry, larval stress has proven a critical influence on adult phenotype, which in turn is strikingly correlated with a suite of life history traits including vector competence (De Jesus and Reiskind, 2016; Honek, 1993; Mourya et al, 2004; Ponlawat and Harrington, 2007; Price et al, 2015; Schluter et al, 1991; Vantaux et al, 2016). In a previous study, our laboratory demonstrated the G × E influence of larval stress on adult body size (Schneider et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…aegypti females, there was no effect of female body size on the average number of spermathecae positive for sperm. De Jesus and Reiskind (2016) found no correlation between female size and number of stored sperm for either Ae. aegypti and Ae.…”
Section: Discussionmentioning
confidence: 86%
“…albopictus colonized from the southern United States, most mated females contained sperm in two spermathecae, except for a few Ae. albopictus that had sperm in three (De Jesus & Reiskind, 2016). Among wild-caught specimens from Florida, Tripet et al (2011) found that most Ae.…”
mentioning
confidence: 99%